TINGKAT BAHAYA EROSI DENGAN METODE USLE DI DAS BAYANG SANI KABUPATEN PESISIR SELATAN - Situmeang, Frans T Gunawan; Hermon, Dedi; Zahara, Leni (Pendidikan Geografi, 2013)
The research was done at the watershedÂ  Bayang Sani district Pesisir Selatan in order to determine the level of erosion hazard with the USLE method (Universal Soil Loss Equation) and the spatial distribution of erosion potential in the study area . The method used was a survey method with mapping unit. Mapping unit is a unit of land that was obtained from the overlay map unit land form, slope, geology, soil and land use.Sample in the tensile is purposive random sampling. Purposive random sampling is taking a sample as random based on specific objectives. Of 16 land units 3 units of land designated as a sample in order to determine the rate of erosion in the watershed Bayang Sani district pesisir selatan.The results showed erosion factors in the study area are as follows: erosivity (R) 2176.22 mm / bl , erodibility ( K ) 0.65 to 0.99 , and slope length ( LS ) 9.34 to 34.54 , land cover and conservation measures ( CP ) 0.010 to 0.200 then calculated using the USLE method of erosion potential in the area of research that is very heavy on land units F3.II.Kc.Qal.Lat, V2.II.Kc.Tomp.Lat and V2.II.Sm.Tomp.Lat. The loss of land between 20.10 to 66.35 tonnes / ha / yr spatial distribution of erosion potential is very severe erosion hazard rate spread in the southern part of the study area with land units F3.II.Kc.Qal.Lat, and in the middle study area with land units and V2.II.Sm.Tomp.Lat V2.II.Kc.Tomp.Lat. Total rate of erosion in the study area of 122.66 tonnes/ha/yr.